Genetic determinants of cellular addiction to DNA polymerase theta - Wanjuan Feng (Nature Portfolio, 2019)
Polymerase theta is a widely conserved DNA polymerase that mediates Theta Mediated End Joining. Here authors present a synthetic lethal CRISPR screen to identify DDR gene mutations that induce cellular addiction to Pol theta.